Dapagliflozin Protection against Myocardial Ischemia by Modulating Sodium-glucose Transporter 2 Inhibitor, Silent Information Regulator 1, and Fatty Acid Synthase Expressions - Sweed, Eman; Sweed, Dina; Galal, Nader; Abd-Elhafiz, Huda Ibrahim (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The emerging role of sodium-glucose transporter 2 (SGLT2) inhibitors drugs as potential therapeutic agents in myocardial ischemic (MI) injury treatment has raised the concern for possible mechanisms of action. AIM: The current experimental study aimed to investigate the possible protective effects of dapagliflozin (DAPA) a SGLT2i, on isoproterenol (ISO)-induced MI in rats. MATERIALS AND METHODS: Thirty Wistar rats were divided randomly and equally into three groups. Group 1 (control group): Received 1.0 mL of normal saline through an orogastric tube for 14 days. Group 2 (ISO group): Received 1.0 mL of normal saline orally through an orogastric tube for 14 days. In the last 2 days (days 13 and 14), ISO (100 mg/kg) was freshly dissolved in normal saline and injected subcutaneously once daily. Group 3 (ISO + DAPA-treated group): Received DAPA 1.0 mg/kg/day orally for 14 days. In the last 2 days (days 13 and 14), ISO (100 mg/kg) was introduced like that described in Group 2. RESULTS: DAPA protects MI development by reversal of blood pressure changes, electrocardiographic alterations, stabilization of cardiac enzymes, inflammation restoration, oxidative stress, and lipid profile. SGLT2 was overexpressed in the ISO-induced MI, which declined in the ISO + DAPA group. Moreover, DAPA induced silent information regulator 1 (SIRT1)/fatty acid synthase (FASN) overexpression in ISO-induced MI. DAPA could have a potential protective role against acute MI. CONCLUSION: DAPA protects against acute MI by modulating SIRT1 and FASN expression in cardiac muscles, suppressing oxidative stress, and downregulating inflammatory mediators.